PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI DAN PARTISIPASI MANAJEMEN TERHADAP EFEKTIVITAS SISTEM INFORMASI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KERINCI: Afriyanti - AFRIANTI, SE., M.Pd (LPPM STIA Nusantara Sakti, 2022)
The formulation of the problem, is there an effect of sophistication in information technology and management participation on the effectiveness of information systems at the Department of Population and Civil Registration of Kerinci Regency, either partially or simultaneously. The purpose of this study was to determine the influence and magnitude of the influence of sophistication of information technology and management participation on the effectiveness of information systems at the Department of Population and Civil Registration office at Kerinci Regency. The data respondents in this study were 32 respondents using a quantitative approach, where the analysis tool was using the coefficient of determination above showing the magnitude (R²) was 0.915 (there was an effect of the two dependent variables from the correlation coefficient 0.915) this means 91.5 % variation in Information System Effectiveness can be explained by variations of the 2 independent variables, namely Information Technology Sophistication () and Management Participation (), while the remaining 8,5% (100%-91,5%) is influenced by other variables that are not researched. This is also evidenced by the obtained Ftes test, it turns out that the value of F = 156,453 With a significant level less than 0.05 (0.000 < 0.05) then Ho is rejected and Ha is accepted, meaning that together there is a significant influence between Information Technology Sophistication () and Management Participation () on the Effectiveness of Information Systems (Y) at the Department of Population and Civil Registration.